The Effect of Skating on Balance and Functional Mobility of Children with Autism Disorder in Kerman - Torabi, Farnaz; Abdolkarimi Ravari, Mohadeseh; Zamankhanpour, Mahdiyeh (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to investigate the effects of an 8-week skating intervention on balance and functional mobility in children with ASD in Kerman, Iran. Methods and Materials: A semi-experimental pretest–posttest design with a control group was employed. Twenty children aged 7–8 years with ASD were randomly assigned to either an experimental group (n=10) or a control group (n=10). The experimental group participated in supervised skating sessions three times per week for eight weeks. Assessments included static balance (modified Stork test), dynamic balance (heel-to-toe walking test), Timed Up and Go (TUG), Six-Minute Walk Test (6MWT), and Timed Floor-to-Stand (TFTS). Measurements were taken at baseline and after the intervention. Data were analyzed using paired t-tests and ANCOVA, with a significance level set at p<0.05. Findings: Post-intervention, the experimental group demonstrated significant improvements in static balance, dynamic balance, TUG performance (reduced time), 6MWT (increased distance), and TFTS (reduced time), while the control group showed no significant changes. Between-group analyses confirmed statistically significant differences in favor of the experimental group. Conclusions: Skating exercises significantly enhance balance and functional mobility in children with ASD. Skating is recommended as an accessible, engaging, and cost-effective intervention within rehabilitation programs for this population. Future studies should explore the long-term cognitive, psychological, and social effects of skating interventions.